Основні технічні характеристики матриць фотоапаратів - Солодов, В. Д. (ХНУРЕ, 2019)
The paper discusses the families of the most common 8 – bit microcontrollers (MC), which have low cost and are suitable for use in products for various purposes. Such microcontrollers are produced by a large number of firms.